ANALISIS FLIGHTDATA RECORDER KECELAKAAN PESAWAT TERBANG A320 UNTUK MENDAPATKAN STALL SPEED DAN PROSES REKONSTRUKSI KECELAKAAN MENGGUNAKAN SOFTWARE FLIGHTSCAPE - Mohammad Ardi Cahyono; Andry Renaldy Pandie (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
Aircraft is transportation mode which in it operation refer to all operation procedure be valid. Although that, accident probability will be occur. To help human/analysts to find out and learn more about aircraft accident causes then black box installed in aircraft. Parameters which recorded by black box still in bynari data type, so it must to be processing using Flightscape software and Google Earth application in order to represented and understood by analysts to help analysis process. It so happens, main purposes from this research are to know stall speed value from aircraft A320 which analyzed. Methods which used to finished this research that is simulation method in Flightscape to get video/animation o f flight accident reconstruction, and analysis method as manually to get stall speed o f aircraft.Based on analysis result, be obtained that aircraft stall speed value is 348,0942 kts (when first stall warning) and 150,8151 kts (when three secons before crash).